Scientific Work Writing Training For Students Of Indragiri Islamic University, Stmik Indragiri, And Stai Auliaurrasyidin Tembilahan - Ridwan, Muannif; Adnan, Indra Muchlis; Amin, Muhammad; Siregar, Vivi Arfiani; Lidar, Goesdery; Andriansyah; Hidayanti, Sri; Herdiansyah (Jurnal Pengabdian Masyarakat (Bisma), 2023)
This article describes the implementation of lecturer service in providing scientific writing training material for students of Universitas Islam Indragiri, STMIK Indragiri, and STAI Auliaurrasyidin Tembilahan. This training is important to add insight into scientific writing techniques in this case writing scientific articles in scientific journals. The partner's problem is that there are still many students who find it difficult to compile or make good scientific articles. Therefore, the purpose of this activity is to make it easier for students and increase their understanding because they will not be separated from writing scientific papers. The implementation of this activity is hybrid (online and offline) and uses lecture and practice methods or accompanied independent assignments for several weeks. The participants who participated in this training were 76 students. This training was welcomed enthusiastically by partners, namely students from 3 (three) universities in Indragiri Hilir Regency. This service activity shows its success, it is proven that there are several students who have succeeded in collaborating in writing scientific papers in the form of journal articles that have been successfully published in several unaccredited and accredited national journals. This means that the proof of performance from the results of this assisted self-assignment is the achievement of the success of this activity. Furthermore, it is recommended to conduct continuous training to hone students' abilities in writing and creating scientific papers.